2019
DOI: 10.2174/1871526519666181123145540
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Ebola Virus VP35 and VP24 Interferon Inhibitory Functions and their Initial Exploitation as Drug Targets

Abstract: Upon viral infection, the interferon (IFN) system triggers potent antiviral mechanisms limiting viral growth and spread. Hence, to sustain their infection, viruses evolved efficient counteracting strategies to evade IFN control. Ebola virus (EBOV), member of the family Filoviridae, is one of the most virulent and deadly pathogen ever faced by humans. The etiological agent of the Ebola Virus Disease (EVD), EBOV can be undoubtedly considered the perfect example of a powerful inhibitor of the host organism immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 138 publications
1
18
0
Order By: Relevance
“…In addition to the ubiquitination-dependent modulation of host immune responses discussed above, we find ubiquitin-dependent degradation to be targeted by SARS-CoV-2. Hijacking the ubiquitin proteasome system is a common trait of almost all viruses (Banks et al, 2003;Fanunza et al, 2019;Tang et al, 2018). Supporting the idea that this is occurring for SARS-CoV-2, we found SARS-CoV-2 viral proteins to target host proteins involved in ubiquitin-mediated degradation.…”
Section: Functions Enriched In a Sars-cov-2/human Virhostome Networksupporting
confidence: 80%
“…In addition to the ubiquitination-dependent modulation of host immune responses discussed above, we find ubiquitin-dependent degradation to be targeted by SARS-CoV-2. Hijacking the ubiquitin proteasome system is a common trait of almost all viruses (Banks et al, 2003;Fanunza et al, 2019;Tang et al, 2018). Supporting the idea that this is occurring for SARS-CoV-2, we found SARS-CoV-2 viral proteins to target host proteins involved in ubiquitin-mediated degradation.…”
Section: Functions Enriched In a Sars-cov-2/human Virhostome Networksupporting
confidence: 80%
“…1,12,13 The ability of EBOV to avoid and inhibit the innate immune response in the early stages of infection is due to the viral multifunctional proteins, VP24 and VP35, 14,15 which are the main determinants of virulence 1618 and thus attractive drug targets. 1924…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of VP24 residues involved in the suppression of the IFN cascade were shown to be responsible for the acquisition of high virulence in animal models (5,10), suggesting VP24 as a validated target for drug development. Hence, identifying a therapy targeting the IFN-I-inhibitory functions of EBOV represents a promising approach to an early control of the infection (11)(12)(13)(14). A number of in silico studies reported molecules potentially able to bind different EBOV targets, including VP24 (15,16), while two recent studies reported that a macrocyclic peptide and a nucleic acid aptamer could antagonize the binding of VP24 and KPN␣ in biochemical assays (17,18).…”
mentioning
confidence: 99%